Expresión de la Proteína Core del Virus de la Hepatitis C en Células HEPG2 Usando el Virus del Bosque de Semliki (2021)
ABSTRACT: The Hepatitis C Virus (HCV) encodes the structural protein Core, which in addition to being the capsid subunit, participates in different mechanisms of HCV infection pathogenesis. Since HCV in vitro replication system has limitations, the use of viral vectors could be a useful tool to study the Core protein properties. To validate the Semliki Forest Virus (SFV) strategy in transduced HepG2 cells to study the HCV Core protein, the expression of green fluorescent protein (GFP) and Core protein expressions were detected 24 to 96 hours post-transduction in HepG2 cells transduced with rSFV. Core protein expression was lower than GFP expression in HepG2 cells. Since HCV Core protein can regulate the activity of the p53 gene, the transcriptional level of this gene was evaluated. A decrease in the level of p53 mRNA was observed in the cells after transduction, compared to the control cells. Although the cells transduced with rSFV-Core had the lowest level of p53 mRNA, the difference was not significant compared to cells transduced with rSFV-GFP. The results confirm that rSFV allows the transient expression of heterologous proteins in human hepatoma cell lines. Additional studies are needed to determine whether the decreased expression of Core may be due to the degradation of the viral protein.